Overconfidence and financial decision making - the impact of financial risk tolerance on confidence judgments - Cagdas, Koray (2017)
A wide range of research has shown that people are overconfident in their judgments displaying a contradiction to modern economic theories supposing individuals as rational agents with the goal of maximizing expected utility and minimizing risk exposure. However, overconfident agents overestimate their judgments and expertise or presume themselves to be better than their peers leading those individuals to exhibit a higher willingness to engage in risky behaviors. So, it can be expected that overconfidence and financial risk tolerance are positively associated with each other. A sample consisting of 137 people was analyzed with the result that there is no evidence supporting this hypothesis, neither in a group level nor on an individual basis. The degrees of overconfidence and risk tolerance are not correlated. Nevertheless, financial risk tolerance has a significant positive correlation on observed level of confidence, whereas accuracy of judgments is not significantly affected by the degree of risk tolerance.